SCIENTIFIC REVIEW OF THE PICTORIAL TAJWEEDI QURAN PREPARED BY PROF. ZAFAR IQBAL SIALKOTI.: پروفیسر ظفر اقبال سیالکوٹی کے تیار کردہ مصحف ’’عکسی تجویدی قرآن مجید‘‘ کا علمی جائزہ - Muhammad Imran Raza Tahavi; Dr. Zeenat Haroon (International Research Journal of Arabic and Islamic Studies, 2021)
Undoubtedly, the Qur'an is the holy book of Allah Almighty, so there is nothing common with this book.The person who became attached to this scripture and who contributed to its service became special.One of these special people is Prof. Zafar Iqbal Sialkoti. Professor Zafar Iqbal served the Holy Quran in a very Nobel contribution.He first produced a copy of the Qur'an before the Partition of India in Lahore by Anjuman-e-Hamayat-e-Islam, which was later called the representative Mushaf version of the Government of Pakistan.Later, Professor Zafar Iqbal personally prepared a Mushaf, which he named Aksi Tajweedi Quran.In this Mushaf, you have specifically adhered to the principles of Ottoman ritual. And this Mushaf was confiscated phonetically, for which a special style of confiscation was adopted which we do not find in any other Mushaf before. Of course, this is a commendable work. His efforts were greatly appreciated.This Mushaf was completed in 1971 after almost 19 years of continuous hard work. And firstly printed by packages Pakistan.This Mushaf is undoubtedly a valuable asset for beginners.